دور إدارة المعرفة في تعزيز فاعلية إدارة علاقات الزبائن لضمان امتلاك مزايا تنافسية: دراسة استطلاعية لآراء المدراء في عينة من الشركات الصناعية العاملة في محافظة نينوى - أثير حسو اسحق (PROSPECTIVE RESEARCHES, 2023)
Organization, due to the current business environment, tries to get knowledge so as to ensure the achievement of competitive advantage in the current markets. The research studies the three main axes: knowledge management, customer relationship management and competitive advantage in an attempt to describe the type of relationship between the levels of engagement and impact. Competitive advantage provides support to the organizations under search, and local organizations to improve their competition position and to improve their relationship with customers and to increase and improve the stock of knowledge which lead to increase market share and profits. The research comes up with a set of conclusions; perhaps the most important one is the growing role of knowledge management when supported by customer relationship management to achieve feature competitive. The researcher recommends that those organizations which seek for survival must have knowledge base that suits the heads and the requirements of both current and future probable customer.